2006
DOI: 10.1593/neo.06493
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Spontaneous Breast Cancer Metastasis by Anti—Thomsen-Friedenreich Antigen Monoclonal Antibody JAA-F11

Abstract: Thomsen-Friedenreich antigen (TF-Ag) is expressed in many carcinomas, including those of the breast, colon, bladder, and prostate. TF-Ag is important in adhesion and metastasis and as a potential immunotherapy target. We hypothesized that passive transfer of JAA-F11, an anti-TF-Ag monoclonal antibody, may create a survival advantage for patients with TF-Ag-expressing tumors by cytotoxicity, blocking of tumor cell adhesion, and inhibition of metastasis. This was tested using in vitro models of tumor cell growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 38 publications
1
106
0
2
Order By: Relevance
“…Since protein-carbohydrate interactions are generally weak, these human scFv proteins with rather high affinities for oncofetal T-antigen have high potential for future development of cancer therapeutics. For example, an anti-T-antigen monoclonal antibody JAA-F11 has been shown to block the adhesion of human and mouse tumor cells in metastatic models in in vitro and in vivo studies (27). Further characterization of 1E8 and 1E6 scFv proteins, their affinity improvement, and their effects on tumor growth and metastasis will be needed for future clinical application of these scFv proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Since protein-carbohydrate interactions are generally weak, these human scFv proteins with rather high affinities for oncofetal T-antigen have high potential for future development of cancer therapeutics. For example, an anti-T-antigen monoclonal antibody JAA-F11 has been shown to block the adhesion of human and mouse tumor cells in metastatic models in in vitro and in vivo studies (27). Further characterization of 1E8 and 1E6 scFv proteins, their affinity improvement, and their effects on tumor growth and metastasis will be needed for future clinical application of these scFv proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Our group showed that a highly specific immunoglobulin IgG 3 monoclonal antibody (MAb) developed against the TF-Ag (JAA-F11) (Rittenhouse-Diakun et al, 1998) impeded TF-Ag binding to vascular endothelium, blocking a primary metastatic step and providing a survival advantage (Heimburg et al, 2006). In addition, in patients, even low levels of antibodies to TF-Ag seem to improve prognosis; thus, it is expected that vaccines generating antibodies toward TF-Ag would be clinically valuable.…”
Section: Nd Generation Tf-vaccinementioning
confidence: 99%
“…CD176 is also expressed in leukemia and lymphoma cells (4,6), and may be a promising prognostic marker in T-cell acute lymphoblastic leukemia (7,8). In addition, CD176 is expressed in some cancer stem cells (9), and it is functionally involved in the liver metastasis process of tumors (1,10), the adhesion of human breast cancer cells to the endothelium (11,12) and the apoptosis of leukemic cells (13). Therefore, CD176 may be a promising target for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Liver colonization of CD176 (TF)-positive syngeneic tumor cells was suppressed by pretreatment with a CD176 (TF) antibody (18). CD176 (TF) antibody markedly inhibited the adhesion of human breast cancer cells to the endothelium and caused an extension of survival time in mice carrying a 4T1 metastatic breast CD176 antiserum treatment leads to a therapeutic response in a murine model of leukemia (12). Based on these observations, we hypothesized that CD176 antibody might have a therapeutic effect on patients with CD176 + cancer.…”
Section: Introductionmentioning
confidence: 99%